Total phenolic content, antioxidant activities and drying optimization of hog plum (Spondias pinnata (Linn. f.) Kurz.) leaves dried using a pilot-scale high performance dryer - Bermido, Catherine Talagtag (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Antioxidants, which can be found in plant leaves, have been reported to reduce the risk of human diseases brought about by free radicals and oxidative stress. The raw leaves of Spondias pinnata, an undervalued edible Philippine plant, were characterized for composition and physicochemical properties. The effect of drying time and temperature on the total phenolic content and free radical scavenging activities were also determined, and the parameters are optimized using response surface methodology. Values of 80.3 ± 0.804, 1.57 ± 0.163, 3.46 ± 0.316, 0.246 ± 0.0128, 0.984 ± 0.111 and 13.8 ± 0.859 g/100g fresh sample were reported for moisture, ash, crude protein, crude fat, crude fiber and available carbohydrates, respectively. Results indicate the potential of S. pinnata leaves as a possible functional food or ingredient. Physicochemical tests of S. pinnata leaves revealed a water activity of 0.909 ± 0.002, pH of 2.62 ±0.026, titratable acidity of 10.9 ± 0.327 g citric acid/ 100 g leaves. Drying had contributed to higher amount of total phenolics and better antioxidant activity compared to raw leaves. Leaves dried at 65°C for 330 minutes had the highest total phenolic content and the highest antioxidant activity. Optimization factors were temperature (35-65°C) and process time (150-330 min) while investigated responses were total phenolic content (TPC), percent loss in total phenolic content (% loss TPC), effective concentration at 50% of DPPH radicals (EC50), moisture content (MC) of 5-15% and water activity (aw) value of below 0.6. The optimum condition was found to be at temperature of 64.77°C with drying time of 231.9 min. At this optimum condition, TPC, % loss TPC, EC50, MC and aw were predicted to be 135.8mg GAE/g, 57.8%, 6.87 mg/ml, 15% and 0.46 respectively.